Breeding in Africa for Africa - International Potato Center (2017)
By July 2016, e orts at CIP-Headquarters in Peru to systematically exploit heterosis were well advanced with testing of hybrid progenies underway following a full cycle of reciprocal recurrent selection (RRS). In Uganda, results on the potential to exploit heterosis con rm selecting strongly for virus resistance using RRS. Genetic gains of 0.3 t/ha/year in storage root yield of released varieties over the years were found across programs in Ghana, Mozambique and Peru. Two improved data collection, storage and analysis tools were introduced to the breeding community of practice: Highly Interactive Data Analysis and Productivity Tools for Breeding (HIDAP) and Sweetpotatobase.